2016
DOI: 10.1021/acs.jpcc.6b02734
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic and Isomorphic Cocrystals of a N-Salicylidene-3-aminopyridine with Dicarboxylic Acids: Tuning of Solid-State Photo- and Thermochromism

Abstract: The crystal structures and optical properties of (E)-2-methoxy-6-(pyridin-3-yliminomethyl)phenol (1), a N-salicylidene-3-aminopyridine, and its 2:1 dimorphic cocrystals with fumaric acid (2 and 3) and succinic acid (4 and 5) were studied at solid state in order to understand the effects of cocrystallization and molecular packing on their photo-and thermochromic behavior. New criteria for prediction of the chromic properties, based on the rationalization of the intermolecular interaction in the crystal, are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 31 publications
(58 reference statements)
2
92
0
Order By: Relevance
“…Although any non‐bonded interaction can be used to generate co‐crystals ( e. g. π ‐ π stacking, Coulombic interactions, etc), directional interactions – hydrogen and halogen bonds (denoted H‐bonds and X‐bonds, respectively) – allow for a better control over the interactions found in the resulting co‐crystals. Previously, some of us have shown experimentally that co‐crystallization affects the thermo‐ and photochromic behaviors of N‐salicylideneanilines (or anils), depending on the coformer (the secondary compound) . Anils are dynamical compounds, whose color changes when triggered by external stimuli .…”
Section: Introductionmentioning
confidence: 99%
“…Although any non‐bonded interaction can be used to generate co‐crystals ( e. g. π ‐ π stacking, Coulombic interactions, etc), directional interactions – hydrogen and halogen bonds (denoted H‐bonds and X‐bonds, respectively) – allow for a better control over the interactions found in the resulting co‐crystals. Previously, some of us have shown experimentally that co‐crystallization affects the thermo‐ and photochromic behaviors of N‐salicylideneanilines (or anils), depending on the coformer (the secondary compound) . Anils are dynamical compounds, whose color changes when triggered by external stimuli .…”
Section: Introductionmentioning
confidence: 99%
“…The calculated value of Φ (dihedral angle between aromatic rings) is 31.4° in the RT structure and 31.7° at LT. Despite having Φ >30°, compound 1 has been reported to present only thermochromic behaviour …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, near‐planar conformations ( Φ <20°) should promote a close‐packed molecular arrangement that would hinder rotational motion in the crystal, resulting in non‐photochromic behaviour . However, a number of studies has shown the limit of such an empirical rule . The first method adopted to obtain solid photochromic forms is the introduction of bulky substituents, such as tert ‐butyl or trityl groups, that can act as space openers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[109,110] Yana nd Fan [65] prepared three cocrystals (donor, cyanostilbene-based isomers,CS1, CS2, CS3;acceptor, 1, 4-bromotetrafluorobenzene carboxylic acid, OFN,a nd 1,4-diiodotetrafluorobenzene) with solvent-responsive luminescence.M oreover,C S2-OFN presents reversible fluorescence on alternating grinding and light illumination. [109,110] Yana nd Fan [65] prepared three cocrystals (donor, cyanostilbene-based isomers,CS1, CS2, CS3;acceptor, 1, 4-bromotetrafluorobenzene carboxylic acid, OFN,a nd 1,4-diiodotetrafluorobenzene) with solvent-responsive luminescence.M oreover,C S2-OFN presents reversible fluorescence on alternating grinding and light illumination.…”
Section: Stimuli-responsive Luminescent Cocrystalsmentioning
confidence: 99%